Generation Z Repurchase Behaviour Analysis of Online Profit Thrift Shop in Indonesia - Nur Yanto, Ananda; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. There are two types of thrift shops, non-profit and profit. In the current era, thrift businesses are starting to emerge, especially online profit thrift shops. This has resulted in an increase in Generation Z customers category online thrift stores over the past few years. Generation Z is known to be quite difficult to encourage do repurchase again at the same shop. Hence, an extra strategy is needed for online thrift store marketers that can encourage consumers to make repurchase intentions at the same online profit thrift store. The researcher explores the factors (perceived usefulness, enjoyment of online stores, trustworthiness of online shops, need for uniqueness, price orientation) of two major dimensions (store image and motif thrift) adopted from related journals. This study will use a survey method in collecting data from respondents and PLS-SEM. The results of this research indicate that enjoyment of online stores, need for uniqueness, and price orientation influences the repurchasing behavior of Generation Z on profit-winning online stores. The results of this research are expected to increase knowledge of the profit thrift store marketers, about generation Z Indonesia and to maximize sales of thrift products online in Indonesia.Keywords: Generation Z, Online Profit Thrift Stores, PLS-SEM, Repurchase Intention